Marriage Governance and Legal Pluralism in Central Asian Family Law Systems - Nurillo Fayzullaevich Imomov; Umida Muminovna Makhmudkhodjayeva; Zavkiddin Aminovich Amonov; Duysenbay Tolybaevich Saparov; Azimjon Abdumumin Ugli Ibrokhimov (Contrarius Indonesia, 2026)
Existing studies insufficiently examine the interaction between state law, Islamic law, and customary norms in determining the validity of marriage, particularly in relation to legal recognition, registration procedures, and the protection of family rights within pluralistic family law systems in Central Asia. This study analyses how different legal systems respond to such pluralism and identifies its implications for legal certainty and social legitimacy. The research applies a normative juridical method with doctrinal and comparative approaches to assess the relationship between national family law frameworks and socio religious norms. The findings indicate that first, Uzbekistan prioritises state registration as the principal determinant of marital validity, thereby emphasising formal legal certainty within its family law system. Second, Indonesia adopts an integrative approach that recognises both religious legitimacy and administrative registration as essential elements in determining marital validity, reflecting a more accommodative model of legal pluralism. Third, these differing approaches demonstrate distinct strategies in balancing legal certainty with prevailing social and religious values, thereby underscoring the importance of regulatory harmonisation to ensure legal protection, institutional coherence, and broader social acceptance of marriage within pluralistic legal systems.